The Effect of Family Support on Exclusive Breastfeeding Success among Primiparous Mothers - Rika Asmirah; Cakrawati R Cakrawati R; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
ABSTRACT Exclusive breastfeeding for the first six months of a baby's life is an important effort in improving the health and growth of the baby. However, the success of exclusive breastfeeding is influenced by various factors, one of which is family support. Emotional support, information, and practical assistance from the family can increase the mother's motivation to provide exclusive breastfeeding. This study aims to analyze the effect of family support on the success of exclusive breastfeeding in primiparous mothers . The study used an analytical design with a cross-sectional approach . The study sample was 70 primiparous mothers with babies aged 0–6 months. Data were collected through interviews using a structured questionnaire. Data analysis used the chi-square test . The results showed that mothers who received good family support had a success rate of exclusive breastfeeding of 78.4%, while mothers with less family support only had a success rate of 41.2%. The results of the statistical test showed a p value = 0.012 (p < 0.05). It was concluded that family support has a significant influence on the success of exclusive breastfeeding in primiparous mothers .